Influence of Regional Transport Mechanisms on the Fingerprint of Biomass-Burning Aerosols in Buenos Aires - Ana G. Ulke (Advances in Meteorology)
The study focuses on the transport of aerosol particles resulting from biomass burning in central South America towards the megacity of Buenos Aires by the South American Low-Level Jet. In particular, the cases are studied in which the exit area of the Jet reaches the La Plata Basin with no precipitation associated, herein called Chaco Jet 1 (CJ1), which could remove aerosols from the atmosphere on their way towards the city. CJ1 events registered within the five-year period of 2001–2005 are examined along with changes in the optical properties of aerosols over the city from measurements from the Aerosol Robotic Network (AERONET) site. Three-dimensional backward trajectories of CJ1 were obtained to verify the connection between the receptor site and the biomass-burning source region. A cluster analysis of the trajectories allows further characterizing the features and impacts of regionally transported aerosols. A subsample of days on which impacts of the contribution of biomass burning could have occurred, showed a statistically significant increase in aerosol optical depth and Ångström exponent, reflected by an increase in the peak of the derived volume size distribution in the fine fraction size range, which also shifts slightly towards bigger radii. The days with AOD greater than 0.15 show overall behaviour like other urban sites with pollution of different origins. The evaluation of the selected data reveals that higher values of AOD and changes in the Ångström exponent are linked to the dispersion of biomass-burning aerosols. Air mass trajectories coinciding with the CJ1 core present the strongest impact on aerosol characteristics, which can be seen in spectral measurements.